By the Honourable Col. Francis Nicholson, and Col. Samuel Vetch. A proclamation : whereas Her Majesty hath been pleased to intrust us with Her royal commands and instructions to the governours of Her several provinces upon the continent of America, who are to furnish their respective quota's towards the present expedition - Nicholson, Francis, 1655-1728 (LLMC-digital (Series), 1709)
Requesting volunteers for the expedition to Canada and Acadia.